Effectiveness of Eco-Enzyme for Increasing Growth and Production of Shallot from Vegetative Seeds - Kesmayanti, Novisrayani; Ruli Joko Purwanto; Romza, Edy; Kalsum, Ummi; Irmawati, Widya; Putri, Kartika (Journal of Agriculture, 2025)
The fluctuating and decreasing production of shallots impacts the national stock. Its cultivation using high inorganic fertilizers requires high costs, reduces soil fertility, and affects long-term production.  Efforts are needed to increase production at a lower cost, reduce the use of inorganic fertilizers, and be more environmentally friendly.  One of them is using eco-enzymes that can be used as fertilizers, soil conditioners, and as a source of plant nutrients.  This study aims to evaluate and analyze the effectiveness and potential of eco-enzymes to increase the growth and production of shallots, while reducing the amount of inorganic fertilizer.  The study used a Randomized Block Design, four replications. There were three levels of treatment: P1 eco-enzyme; P2 eco-enzyme + N, P, K fertilizer 50%; P3 N, P, K fertilizer 100%. Each treatment consisted of 8 experimental units, for a total of 96, with a dose of N= 150 kg urea.ha-1, P= 200 kg SP-36.ha-1 and K= 150 kg KCl.ha-1. Eco-enzyme was given every week with a concentration of 1 ml.l-1; half was given by spraying the plants and half by watering the media.  The results showed that eco-enzyme is effective and can potentially increase the growth and production of shallots and reduce the use of inorganic fertilizers N, P, and K by up to 50%. The eco-enzyme + 50% N, P, K fertilizer produced shallot with the highest number of leaves per bulb and clump, number of bulbs per clump, circumference of bulbs, weight per bulb, and weight of bulbs per clump.